Business plan (model lean canvas) - Strupplová, Lucie (2016)
The well arranged and instructivee business plan is the basic part of every business project.. Currently is very often used the lean canvas model of the business plan. This model shows us very istructively all the factors influencing the project realisation. The dissertation is divided into the two basic parts. In the thoretical were compared the essential forms of the business plan with their differences. The practical part consists of creating the lean canvas model for the progressive company using the UAV and the MAIA application, monitoring the flight of the UAV. The economic data were analyzed and the structured scheme of the project, with the prediction was realized. The lean canvas model was very useful and optimal for this company and it´s project.